Do każdego gestu inny aktor. Ontologia przedmiotów w Ulicy Krokodyli Brunona Schulza i realizacji filmowej braci Quay - MEYER, DOMINIKA (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
A diff erent actor for each gesture.The ontology of objects in Bruno Schulz’s Street of Crocodiles and the fi lms of the Quay brothers Humanism deprived things of the attention they undoubtedly deserve. An anthropocentric way of perceiving the world dominated most movements in contemporary philosophy and classified them as incapacitated products of human practices. Until now object-oriented ontology has focussed predominantly on literature, but it also creates whole new possibilities for film theorists, forcing viewers to change prevailing formulae.